ANALYSIS OF THE SETTLEMENT SERVICE CENTER SYSTEM ON THE EFFECTIVENESS OF KUPANG CITY SPATIAL PLANNING POLICY - Johanes Renolia Lede; Fransina W. Ballo; Olivia Lousie E Tomasowa (Universitas Dharmawangsa Medan, 2026)
The purpose of this study is to analyze the settlement service center system in relation to the effectiveness of spatial planning policy in Kupang City. This study employs a descriptive quantitative approach using scalogram analysis, the Hansen gravity model, and an evaluation of the Kupang City Spatial Plan (RTRW) 2011–2031. The results indicate that the Coefficient of Reproducibility (COR) value is below the feasibility standard (<0.9), showing that the distribution of facilities in Kupang City is still uneven. Gravity analysis reveals that Oebobo and Maulafa Districts have relatively higher levels of accessibility and regional interaction compared to other districts. Meanwhile, several districts still experience limitations in educational, health, and economic facilities. These conditions indicate that the implementation of spatial planning policy has not yet fully aligned with the directions of the Kupang City RTRW 2011–2031. This study recommends the equitable distribution of public facilities, the strengthening of secondary service centers, and the improvement of interregional infrastructure to support balanced development and the effectiveness of spatial planning policy in Kupang City. Keywords: Settlement Service Centers, Effectiveness of Spatial Planning Policy, Scalogram, Gravity Model, RTRW, Kupang City.